Respuesta :
By the chain rule,
[tex]\dfrac{dy}{dx} = \dfrac{dy}{dt} \cdot \dfrac{dt}{dx} = \dfrac{\frac{dy}{dt}}{\frac{dx}{dt}}[/tex]
So first differentiate both x and y with respect to t.
• dx/dt :
[tex]x = \dfrac{\sin^3(t)}{\sqrt{\cos(2t)}} = \sin^3(t) \left(\cos(2t)\right)^{-\frac12}[/tex]
By the product rule,
[tex]\dfrac{dx}{dt} = \dfrac{d(\sin^3(t))}{dt} \left(\cos(2t)\right)^{-\frac12} + \sin^3(t) \dfrac{d\left(\cos(2t)\right)^{-\frac12}}{dt}[/tex]
By the power and chain rules,
[tex]\dfrac{dx}{dt} = \dfrac{d(\sin(t))}{dt} 3\sin^2(t) \left(\cos(2t)\right)^{-\frac12} -\dfrac12 \sin^3(t) \left(\cos(2t)\right)^{-\frac32} \dfrac{d(\cos(2t))}{dt}[/tex]
[tex]\dfrac{dx}{dt} = 3\sin^2(t) \cos(t) \left(\cos(2t)\right)^{-\frac12} -\dfrac12 \sin^3(t) \left(\cos(2t)\right)^{-\frac32} (-2 \sin(2t))[/tex]
We can clean this up a bit and write
[tex]\dfrac{dx}{dt} = \dfrac{3\sin^2(t) \cos(t)}{\sqrt{\cos(2t)}} + \dfrac{\sin^3(t) \sin(2t)}{\sqrt{\cos^3(2t)}}[/tex]
[tex]\dfrac{dx}{dt} = \dfrac{\sin^2(t)}{\sqrt{\cos^3(2t)}} \left(3 \cos(t) \cos(2t) + \sin(t) \sin(2t)\right)[/tex]
• dy/dt : (I'll skip some steps here, the derivative is nearly the same)
[tex]y = \cos^3(t) \left(\cos(2t)\right)^{-\frac12}[/tex]
[tex]\dfrac{dy}{dt} = 3\cos^2(t) (-\sin(t)) \left(\cos(2t)\right)^{-\frac12} + \cos^3(t) \left(-\dfrac12\right) \left(\cos(2t)\right)^{-\frac32} (-2 \sin(2t))[/tex]
[tex]\dfrac{dy}{dt} = -\dfrac{3\cos^2(t) \sin(t)}{\sqrt{\cos(2t)}} + \dfrac{\cos^3(t) \sin(2t)}{\sqrt{\cos^3(2t)}}[/tex]
[tex]\dfrac{dy}{dt} = -\dfrac{\cos^2(t)}{\sqrt{\cos^3(2t)}} \left(3 \sin(t) \cos(2t) - \cos(t) \sin(2t)\right)[/tex]
Finally, we get dy/dx by dividing the two derivatives above:
[tex]\dfrac{dy}{dx} = \dfrac{-\frac{\cos^2(t)}{\sqrt{\cos^3(2t)}} \left(3 \sin(t) \cos(2t) - \cos(t) \sin(2t)\right)}{\frac{\sin^2(t)}{\sqrt{\cos^3(2t)}} \left(3 \cos(t) \cos(2t) + \sin(t) \sin(2t)\right)}[/tex]
[tex]\dfrac{dy}{dx} = -\cot^2(t) \dfrac{3\sin(t)\cos(2t) - \cos(t)\sin(2t)}{3\cos(t)\cos(2t) + \sin(t)\sin(2t)}[/tex]
and by applying some trig identities,
[tex]\dfrac{dy}{dx} = -\cot^2(t) \dfrac{\sin(3t) - 2\sin(t)}{\cos(3t) + 2\cos(t)}[/tex]
[tex]\boxed{\dfrac{dy}{dx} = -\dfrac{\cos(3t)}{\sin(t) (2\cos(2t) + 1)}}[/tex]
Answer:
[tex]$\frac{dy}{dx}=-\cot (3 t)$[/tex]
Very important note!
Both answer are correct, the thing is: the expression can be more simplified as
[tex]\sin(t)(2\cos(2t)+1) = \sin(3t)[/tex]
that will lead the the answer I just gave.
Step-by-step explanation:
The question is looking for [tex]\dfrac{dy}{dx}[/tex]
We have
[tex]x = \dfrac{\sin^3 (t)}{\sqrt{\cos(2t)}} \quad \text{ and } \quad y = \dfrac{\cos^3 (t)}{\sqrt{\cos(2t)}}[/tex]
One approach would be calculating [tex]\dot{x}[/tex] and [tex]\dot{y}[/tex] considering
[tex]\dfrac{dy}{dx} = \dfrac{\frac{dy}{dt}}{\frac{dx}{dt}}[/tex]
We would have
[tex]$\frac{dx}{dt}=\frac{3 \sin ^2(t) \cos(t)}{\sqrt{\cos (2 t)}} + \frac{\sin (2 t) \sin ^3(t)}{\cos ^{3/2}(2 t)} $[/tex]
[tex]$= \frac{\sin^{2} t}{\cos ^{3/2}(2 t)}(3\cos (t) \cos(2t)+2\sin^{2} (t) \cos(t))$[/tex]
[tex]$=\boxed{ \frac{\sin ^2(t) (2 \cos (t)+\cos (3 t))}{\cos ^{3/2}(2 t)}}$[/tex]
===============================================
[tex]$\frac{dy}{dt}=\frac{\sin (2 t) \cos ^3(t)}{\cos ^{\frac{3}{2}}(2 t)}-\frac{3 \sin (t) \cos ^2(t)}{\sqrt{\cos (2 t)}}$[/tex]
[tex]$= \frac{\cos^{2} t}{(\cos ^{3/2}(2 t)} (-3\sin (t) \cos (2t)+2\cos^{2} (t) \sin (t))$[/tex]
[tex]$=\boxed{ \frac{\sin (t)-\sin (5 t)}{4 \cos ^{3/2}(2 t)}}$[/tex]
Finally,
[tex]$\frac{dy}{dx}= \frac{\sin (t)-\sin (5 t)}{4 \cos ^{3/2}(2 t)} \cdot \frac{\cos ^{3/2}(2t) }{ \sin ^2(t) (2 \cos (t)+\cos (3 t))}$[/tex]
[tex]$=\frac{\cos(t)(2\cos^{2} t-3(2\cos^{2} t-1))} {\sin(t)(2\sin^{2} t+3(1-2\sin^{2} t))} $[/tex]
[tex]$=-\frac{4\cos^{3} (t)-3\cos (t)}{3\sin (t)-4\sin^{3} (t)} $[/tex]
[tex]$=-\frac{\cos (3t)}{\sin (3t)}$[/tex]
[tex]=\boxed{-\cot (3t)}[/tex]